Modeling The Effect of Particle Size on Magnetic Nanoparticles using Modified Ising Model - Christian Fredy Naa (Indonesia Journal on Computing (Indo-JC), 2019)
In this article, the Ising model has been modified to simulate the effect of particle size on magnetic nanoparticles properties especially hole-doped manganites. The objective of this research is to give an insight and clear understanding about magnetic nanoparticles especially the effect of the particle size. The model considers common accepted magnetic nanoparticles theoretical model where each particle consists of core and surface/boundary part. The model mimics the particles size as a clusters or group of spins. The spins were designated as either core or boundary particles and differs for their exchange energy. The model predicts magnetization, coercivity, hysteresis and magnetic characteristics of core and boundary of the nanoparticles. The results are in a good agreement qualitatively with experimental results. The model also gives insight to the micro-states of the spin at each clusters for zero-field-cooled experiment.